Analysis of Sound Propagation Behaviors for Supersonic Jet on Far Field Region by Computational Aero-Acoustics (CAA) Simulation - Maulana, Yudi; Manshoor, Bukhari; Khalid, Amir; Zaman, Izzuddin; Didane, Djamal Hissein; Abdul Haq, Reazul Haq; Kamarudin, Kamarul-Azhar; Nurmutia, Syahreen; Saleman, Abdul Rafeq; Rathje, Rio Marco; Rothe, Christin; Ibrahim, Mohd Nizam (semarak ilmu, 2024)
Noise emission is an essential issue for the aviation industry, as it harms health and induces various physiological responses. The noise generated by supersonic jets is very intense. It will cause fatigue and even damage the human hearing system in the surrounding area of jet operation. Besides, the experimental and prototyping cost for the jet model is prohibitive, and it is a vast project and process that takes a lot of time to run. The purpose of this study is to determine the sound propagation behaviours of a supersonic jet in the far-field region and to analyse the consequences of the velocity of a supersonic jet on sound propagation of supersonic jet by using computational fluid dynamics (CFD) and computational aeroacoustics (CAA) simulations. This study focused on the perspective of observing the distance of the receiver when receiving the sound propagation of a supersonic jet, the observed angle of the receiver when receiving the sound propagation of a supersonic jet, and the velocity of the supersonic jet. The CFD and CAA analyses were performed in transient state simulation and the 2-inch Acoustics Reference Nozzle (ARN2). The result shows that the overall SPL throughout the frequency is proportional to the jet velocity of the supersonic jet. However, the distance and angle of the receiver gave different results in sound propagation behaviour. The results also conclude that as the distance between the receiver and jet nozzle exit increases, the overall SPL trend will decrease throughout the frequency increase. As the vertical distance between the receiver and the axisymmetric line of the jet nozzle increases, the frequency of the receiver starts to observe will decrease.